Critical thinking and decision-making skills regarding reproductive health among pupils in Central Java - Bagoes Widjanarko; Ratih Indraswari; Novia Handayani; Aditya Kusumawati (Intelektual Pustaka Media Utama, 2023)
Many teenagers are entangled in promiscuity which results in unwanted pregnancies, early marriages, or abortions. How a teenager decides something in their life is influenced by their previous experience and environment. This study aims to determine the critical thinking and decision-making skills of pre-adolescence children in terms of reproductive health. This research is a cross- sectional study conducted on 12,689 pupils in Semarang, Central Java Province, Indonesia. The proportion of respondents based on sex and grade is quite balanced. As many as 49% of the pupils lack knowledge and a permissive attitude (52.5%) about reproductive health. Of 50% of pupils have low critical thinking skills and only 61.4% have good decision-making skills. Girls have better critical thinking skills than boys (p=0.004). Knowledge affects critical thinking and decision-making skills in pupils (OR=1.2). Pupils who can think critically tend to have good decision-making skills (p<0.001, OR=5.1). Decision-making skills in children are influenced by critical thinking skills. Both are influenced by knowledge. The health and education offices need to collaborate to increase pupils’ health and reproductive knowledge.